Interaction of textile variability and flow channel distribution systems on flow front progression in the RTM process. (March 2018) - Kracke, C.; Nonn, A.; Koch, C.; Nebe, M.; Schmidt, E.; Bickerton, S.; Gries, T.; Mitschang, P.
Abstract: The high volume production of carbon fibre reinforced plastics needs cost efficient and robust processes. This paper investigates the influence of local textile variation on flow front progression in resin transfer moulding (RTM). To quantify the textile variation, the textile has been tested with laser triangulation, to achieve the thickness profile map of the flat textile preform. This preform is placed in a transparent flow visualisation tool and an oil is injected into the mould via two different flow channel distribution systems. The flow front progression of the fluid is continuously measured from both sides with two cameras. Furthermore, to demonstrate the influence of defects like folds from the draping process on the local filling behaviour, the textile is prepared with an artificial fold, made of additional non-crimp fabric (NCF) strips. The results show how different defects in the textile influence the local filling behaviour and how the additional flow channel distribution system can decrease the effect of these defects.